Physical activity in pre-school children: Trends over time and associations with body mass index and screen time - Fotini Venetsanou; Antonis Kambas; Vassilios Gourgoulis; Mary Yannakoulia (Taylor & Francis Group, 2019)
Background: Pre-school years are important for adopting health behaviours; however, today's children seem to be overweight, present low physical activity (PA) levels and exceed screen time (ST) recommendations. Aim: To examine (a) time trends in PA in Greek pre-school children, (b) the associations among PA, body mass index (BMI) and ST and (c) potential PA differences between boys and girls. Subjects and methods: Data from five cross-sectional cohorts (2005 [n = 252]; 2008 [n = 212]; 2011 [n = 187]; 2014 [n = 194]; 2017 [n = 128]) were compared. PA was assessed using Omron HJ-720IT-E2 pedometers, whereas ST was reported by participants' parents. A 4-way ANOVA was applied on children's average week step counts. Results: A significant association (F = 828.90, p < 0.001, η2 = 0.638) between ST and PA was revealed, with children that had ST < 1 hour/day presenting the higher PA levels and being the only ones that met PA recommendations (11,500 steps/day). Statistically significant PA differences, though of no practical importance, were found among cohorts. There were no significant PA differences between boys and girls or among BMI categories. Nevertheless, obesity prevalence was found to exist at alarming levels (24.5% in 2008-41.4% in 2017), and a large percentage of children (23.6% in 2008-63.3% in 2017) presented excessive ST (> 2 hours/day). Conclusion: Effective interventions aiming at reducing ST and enhancing PA seem imperative if children's health is to be safeguarded.